Towards an effective collaboration between the South Western Sydney Local Health District and local councils: insights from a qualitative study - Vilas Kovai; Zeenat Mahjabeen; Bin Jalaludin; Francis Fox (BMC, 2022)
Abstract Background Partnership between local government and local health districts is imperative, given their overlapping goals. However, the need for further evidence-informed actions to address health inequities remains. The effectiveness of such partnerships requires better insight into how local governments perceive partnerships with local health districts, and how well equipped and prepared they are to deal with the health equity opportunities and challenges. It was precisely for these reasons that a qualitative study was conducted by South Western Sydney Local Health District (SWSLHD) in 2016. Objective This study aims to better understand how to improve the effectiveness of collaboration between local governments and the public health sector. Methods Qualitative data were collected from 14 in-depth interviews with staff representing five of the local councils comprising SWSLHD. These data were then thematically analysed using inductive and deductive reasoning through the application of NVivo software. Results While councils recognize the potential value of consulting SWSLHD, limited communication and the absence of a clearly defined process for collaboration needs to be addressed. Moreover, councils perceive knowledge gaps in relation to basic issues, such as who provides what services to whom, and how to access local-government-level data from health experts. Conclusions The study confirms the importance of providing locally relevant public health data to help address issues of mutual concern that arise during the consultation process. Moreover, it suggests that proactive and ongoing consultation between SWSLHD and councils is critical if there is to be effective engagement, and coordinated and sustained action. The concerns raised in this study echo findings from studies from other local government settings of Victoria, South Australia and New South Wales. Thus, the study findings may be applied to other councils beyond the SWSLHD.